2021
DOI: 10.3390/app11072995
|View full text |Cite
|
Sign up to set email alerts
|

Application Ranges of EPB Shield TBM in Weathered Granite Soil: A Laboratory Scale Study

Abstract: Soil conditioning is a key factor in increasing tunnel face stability and extraction efficiency of excavated soil when excavating tunnels using an earth pressure balance (EPB) shield tunnel boring machine (TBM). Weathered granite soil, which is abundant in the Korean Peninsula (also in Japan, Hong Kong, and Singapore), has different characteristics than sand and clay; it also has particle-crushing characteristics. Conditioning agents were mixed with weathered granite soils of different individual particle-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been shown that proper soil conditioning can effectively prevent spewing [4,5] . Many scholars have analyzed the role of conditioning agents and proposed applications for different conditioned soils [6][7][8][9]. Jin D et al [10] analyzed soil transport inside a screw conveyor based on CFD, and gave a spewing damage surface controlled by the properties of the soil when the pressure at the outlet of the screw conveyor is atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that proper soil conditioning can effectively prevent spewing [4,5] . Many scholars have analyzed the role of conditioning agents and proposed applications for different conditioned soils [6][7][8][9]. Jin D et al [10] analyzed soil transport inside a screw conveyor based on CFD, and gave a spewing damage surface controlled by the properties of the soil when the pressure at the outlet of the screw conveyor is atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%